Interreader agreement of PI‐RADS v. 2 in assessing prostate cancer with multiparametric MRI: A study using whole‐mount histology as the standard of reference. Issue 2 (5th September 2018) - Girometti, Rossano; Giannarini, Gianluca; Greco, Franco; Isola, Miriam; Cereser, Lorenzo; Como, Giuseppe; Sioletic, Stefano; Pizzolitto, Stefano; Crestani, Alessandro; Ficarra, Vincenzo; Zuiani, Chiara
Abstract : Background: Most studies assessing interreader agreement of Prostate Imaging Reporting and Data System v. 2 (PI‐RADS v2) have used biopsy as the standard of reference, thus carrying the risk of not definitively noting all existent cancers. Purpose: To evaluate the interreader agreement in assessing prostate cancer (PCa) of PI‐RADS v2, using whole‐mount histology as the standard of reference. Study Type: Monocentric prospective cohort study. Population: In all, 48 patients with biopsy‐proven PCa referred for radical prostatectomy, undergoing staging multiparametric magnetic resonance imaging (mpMRI) between May 2016 to February 2017. Field Strength/Sequence: 3.0T system using high‐resolution T2 ‐weighted imaging, diffusion‐weighted imaging (echo‐planar imaging with maximum b‐value 2000 sec/mm 2 ), and dynamic contrast‐enhanced imaging (T1 ‐weighted high resolution isotropic volume examination; THRIVE) Assessment: Three radiologists blinded to final histology (2–8 years of experience) analyzed mpMRI images independently, scoring imaging findings in accordance with PI‐RADS v2. On a per‐lesion basis, we calculated overall and pairwise interreader agreement in assigning PI‐RADS categories, as well as assessing malignancy with categories ≥3 or ≥4, and stage ≥pT3. Statistical Tests: Cohen's kappa analysis of agreement. Results: On 71 lesions found on histology, there was moderate agreement in assigning PI‐RADS categories to all cancers (k = 0.53) and clinically significant cancers (csPCa) (k = 0.47). Assessing csPCa with PI‐RADS ≥4 cutoff provided higher agreement than PI‐RADS ≥3 cutoff (k = 0.63 vs. 0.57). Interreader agreement was higher between more experienced readers, with the most experienced one achieving the highest cancer detection rate (0.73 for csPCa using category ≥4). There was substantial agreement in assessing stage ≥pT3 (k = 0.72). Data Conclusion: We found moderate to substantial agreement in assigning the PI‐RADS v2 categories and assessing the spectrum of cancers found on whole‐mount histology, with category 4 as the most reproducible cutoff for csPCa. Readers' experience influenced interreader agreement and cancer detection rate. Level of Evidence : 2 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019;49:546–555.